No pain, no gain: an exploratory within-subjects mixed-methods evaluation of the patient experience of sleep restriction therapy (SRT) for insomnia. - Kyle, S; Morgan, K; Spiegelhalder, K; Espie, C (2011)
OBJECTIVE: To explore the patient experience of Sleep Restriction Therapy (SRT) for insomnia, with particular focus on elucidating possible side-effects, challenges to adherence and implementation and perceptions of benefit/impact. METHODS: To fully investigate the patient experience of sleep restriction therapy for insomnia we designed a within-subjects mixed-method study, employing sleep and daytime functioning questionnaires, assessments of sleep-restriction-related side-effects, prospective qualitative audio-diaries and post-treatment semi-structured interviews. University of Glasgow Sleep Centre. Eighteen patients with Primary Insomnia (mean age=42; range 18-64). Patients took part in a 4-week brief sleep restriction intervention, involving two group sessions and two subsequent follow-up phone calls in the home environment. MEASUREMENTS AND RESULTS: Sleep diaries and global measures of insomnia severity and sleep quality, as expected, demonstrated robust improvements at both post-treatment and 3-month follow-up (all large effect sizes). Daytime functioning/health-related quality of life variables similarly evidenced strong treatment effects (moderate to large effect sizes). Reported side-effects were common, with ≥50% of patients reporting impairment in 8 out of 12 listed symptoms as a consequence of initiating treatment. The four most common side-effects were 'fatigue/exhaustion' (100%), 'extreme sleepiness' (94%), 'reduced motivation/energy' (89%) and 'headache/migraine' (72%) [Mean number of symptoms per patient=7.2 (2.4); range 3-11]. Intriguingly, both side-effect frequency and ratings of side-effect interference were associated with baseline to post-treatment improvements in sleep quality. Qualitative real-time audio-diaries during week 1 of treatment and post-treatment interviews provided rich accounts of side-effects associated with acute SRT implementation; general challenges surrounding treatment implementation and adherence/non-adherence; and modifications to sleep parameters, daytime functioning and perceptions of sleep/sleep period. CONCLUSIONS: This work has important implications for the delivery of SRT, particularly concerning awareness of possible 'adverse events' and likely implementation/adherence challenges. Findings also pave the way for testable hypotheses concerning possible mechanisms of action involved in sleep restriction treatment.